ANALYSIS OF FACTORS AFFECTING THE LEVEL OF COMMUNICATIVE INTERACTION OF PUBLIC ADMINISTRATION BODIES - JAIN PRADEEP, Kumar; GAVKALOVA, Nataliia; LYTOVCHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main factors influencing the level of communicative interaction of public administration bodies. It was determined that ensuring communicative interaction is a complex dynamic process focused on maximum interaction with the external environment and adaptation to it of the opportunities permanently inherent in the government and society. It is substantiated that the provision of communicative interaction is a complex dynamic process focused on maximum interaction with the external environment and adaptation to it of the opportunities permanently inherent in the government and society. The external and internal factors that have a direct and indirect influence on the communication interaction of the government and society have been identified. Today, the development of society is characterized by new features of the main social processes and is distinguished by the fact that the modern information environment develops through the improvement of social structures and social institutions. The systematization of influencing factors on the level of ensuring communicative interaction of public administration bodies was studied. It has been proven that the technological support of public administration thanks to information and communication technologies becomes a decisive factor in social evolution. Taking into account the identified factors of influence on the level of ensuring communicative interaction between the authorities and society will contribute not only to the formation of a successful constructive dialogue with the aim of ensuring the stability of the existing order, but also to a more correct justification of the corresponding communicative strategy. In addition, it will be possible to take into account restrictive and restraining measures, and to implement existing opportunities for communication between the authorities and society. It is substantiated that in the framework of ensuring communicative interaction, the following are important: a high level of responsibility and reporting for the preparation and implementation of management decisions; provision of services by creating a transparent system of public service personnel management; strengthening the responsibility of state administration subjects for the results of their activities. The selected factors were ranked and evaluated according to the scale and their impact on the level of ensuring communicative interaction in the public sector was assessed.